2022
DOI: 10.1002/lary.30353
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Corticosteroid Treatment on Recovery of Long‐Term Olfactory Dysfunction Due to COVID‐19

Abstract: Background and Aims Olfactory dysfunction is a recognized manifestation in patients infected with Coronavirus Disease 2019 (COVID‐19). This investigation aimed to assess the effect of mometasone furoate intranasal spray on the improvement of smell dysfunction in post‐COVID‐19 patients. Materials and Methods This randomized placebo‐controlled trial included 80 non‐hospitalized adult patients who had persistent anosmia or severe microsmia for more than 4 weeks due to COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
0
15
1
Order By: Relevance
“…In contrast, Hosseinpoor et al showed a beneficial effect of topically administered mometasone furoate after four weeks of application [ 28 ]: in patients with subacute olfactory dysfunction due to COVID-19, olfaction recovered significantly more in the study compared to the placebo control group when assessed both subjectively and psychophysically using the UPSIT.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Hosseinpoor et al showed a beneficial effect of topically administered mometasone furoate after four weeks of application [ 28 ]: in patients with subacute olfactory dysfunction due to COVID-19, olfaction recovered significantly more in the study compared to the placebo control group when assessed both subjectively and psychophysically using the UPSIT.…”
Section: Discussionmentioning
confidence: 99%
“…We have read the trial by Hosseinpoor et al 1 analyzing the efficacy of nasal corticosteroids (NCs) in the treatment of long‐lasting COVID‐19 related olfactory disorders (OD). Authors concluded that NC may have a positive effect on the recovery process.…”
mentioning
confidence: 99%
“…The outcomes showed that severe chronic anosmia as measured by COVID-19 improved more quickly when Mometasone Furoate nasal spray was combined with olfactory training. In yet another study, it was demonstrated that the frequency of anosmia was reduced by 22.9% when compared to the control group [ 82 ].…”
Section: Nasal Spray For Covid-19 Treatmentmentioning
confidence: 99%